Governing Inflation: Price and Atmospheres of Emergency. (March 2015) - McCormack, Derek
Relative price stability is central to the security of valued forms of life in contemporary liberal democracies, and disruptions to price stability can be and have been understood and experienced as emergencies. However, while the relation between price and emergency can be understood in juridico–political terms, this article argues for the importance of attending to the affective dimensions of this relation. This argument is developed through a discussion of the affective life of price in relation to the disruptive event of inflation, an event characterized by an atmosphere of emergency that takes place as a disturbance of the rhythms and relations of which everyday life consists. Haunted by the spectre of this emergency, governing price in liberal democracies needs to be understood not only through regulatory measures designed to act directly upon price, but also in terms of efforts to act upon the affective spacetimes from which price-emergencies can emerge.